APLIKASI AGLOMERASI MENGGUNAKAN CAO DAN OLI BEKAS DALAM UPAYA PENINGKATAN NILAI KALORI BATUBARA SUB-BITUMINOUS - Setiarto Pratigto; Gladis Chertins Angel; Eriek Aristya Pradana Putra; Dewi Purnama Sari (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Coal is an energy source with enormous benefits, especially in the industrial world. Coal in Indonesia is mostly used as fuel for power plants. The use of low-calorie coal as fuel produces elements of impurities that will increase the ash and sulfur content of low-calorie coal combustion. So that it can cause exhaust gas emissions in the form of SOX, CO, and NOX. Agglomeration is one of the desulfurization technologies by washing clean coal in increasing the calorific value of coal by washing coal physically and chemically with the addition of water and oil as a separator. The purpose of this study was to determine the increase in the calorific value of coal after the agglomeration process. The results of agglomeration with CaO media and used oil can increase the calorific value of sub-bituminous coal with an average effectiveness of 21.49%. The average calorific value of coal samples after agglomeration increased from 5808 Cal/g to 7056.05 Cal/g.